Delineation of polar localization domains of Agrobacterium tumefaciens type IV secretion apparatus proteins VirB4 and VirB11. Issue 5 (13th September 2014) - Das, Aditi; Das, Anath
Abstract Agrobacterium tumefaciens transfers DNA and proteins to a plant cell through a type IV secretion apparatus assembled by the VirB proteins. All VirB proteins localized to a cell pole, although these conclusions are in dispute. To study subcellular location of the VirB proteins and to identify determinants of their subcellular location, we tagged two proteins, VirB4 and VirB11, with the visual marker green fluorescent protein (GFP) and studied localization of the fusion proteins by epifluorescence microscopy. Both GFP‐VirB4 and GFP‐VirB11 fusions localized to a single cell pole. GFP‐VirB11 was also functional in DNA transfer. To identify the polar localization domains (PLDs) of VirB4 and VirB11, we analyzed fusions of GFP with smaller segments of the two proteins. Two noncontiguous regions in VirB4, residues 236–470 and 592–789, contain PLDs. The VirB11 PLD mapped to a 69 amino acid segment, residues 149–217, in the central region of the protein. These domains are probably involved in interactions that target the two proteins to a cell pole.